2023
DOI: 10.1007/s10554-023-02823-z
|View full text |Cite
|
Sign up to set email alerts
|

Extended reality for procedural planning and guidance in structural heart disease – a review of the state-of-the-art

Abstract: Extended reality (XR), which encompasses virtual, augmented and mixed reality, is an emerging medical imaging display platform which enables intuitive and immersive interaction in a three-dimensional space. This technology holds the potential to enhance understanding of complex spatial relationships when planning and guiding cardiac procedures in congenital and structural heart disease moving beyond conventional 2D and 3D image displays. A systematic review of the literature demonstrates a rapid increase in pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Rapid developments in 3D innovative technologies, including VR, AR, and MR, have further advanced the roles of traditional image visualizations in cardiovascular disease and patient care, with increasing studies proving their educational and clinical value in cardiovascular medicine. Due to complex cardiovascular anatomical and pathological aspects and the importance of lifelong learning and training required to deliver highquality standards in cardiovascular care, these 3D visualizations serve as useful tools for healthcare providers and patients [64][65][66][67][68]105,[173][174][175][176][177][178][179][180][181][182].…”
Section: Cardiovascular Ct: Vr Ar and Mrmentioning
confidence: 99%
See 2 more Smart Citations
“…Rapid developments in 3D innovative technologies, including VR, AR, and MR, have further advanced the roles of traditional image visualizations in cardiovascular disease and patient care, with increasing studies proving their educational and clinical value in cardiovascular medicine. Due to complex cardiovascular anatomical and pathological aspects and the importance of lifelong learning and training required to deliver highquality standards in cardiovascular care, these 3D visualizations serve as useful tools for healthcare providers and patients [64][65][66][67][68]105,[173][174][175][176][177][178][179][180][181][182].…”
Section: Cardiovascular Ct: Vr Ar and Mrmentioning
confidence: 99%
“…In the context of cardiovascular disease, the applications of VR and AR mainly lie in the field of interventional cardiology for the purposes of procedural simulation and training, such as planning or simulating TAVR, CHD, or valvular interventions; left atrial appendage occlusion; and/or cardiac ablation procedures [105,[174][175][176][177][178][179][180][181][182]. Studies have shown that the use of VR-/AR-guided approaches can result in more successful attempts with fewer distance errors, shorter navigation times, and shorter path lengths during valvular interventional procedures [65,105]. These techniques are showing great potential for integration into cardiac catheterization laboratories, although more robust studies including more patients are needed.…”
Section: Cardiovascular Ct: Vr Ar and Mrmentioning
confidence: 99%
See 1 more Smart Citation
“…VR immerses surgeons in realistic surgical scenarios using interactive virtual 3D environments [72][73][74]. Conversely, the AR system overlays virtual information in a real-world environment by transposing anatomical structures, surgical plans and intraoperative guidance into the surgeon's field of view [42,75]. Cattapan et al performed an observational study involving cardiac surgery residents to assay the role of surgical simulation on 3D cardiac models as a promising innovative tool to improve understanding of cardiac anatomy, facilitate hands-on learning and enhance proficiency in surgical techniques and confidence levels when performing cardiac surgery [76].…”
Section: Artificial Intelligence and Machine Learning Applied To Cong...mentioning
confidence: 99%
“…In recent years, the development of immersive technologies has been remarkable [32,33]. Their adoption, across a wide spectrum of socio-economic life, is expected to increase steadily, especially as we enter the age of virtual worlds and metaverses [34][35][36][37][38][39]. Extended reality (XR) is characterized by augmented reality (AR), virtual reality (VR), and mixed reality (MR).…”
Section: Introductionmentioning
confidence: 99%